Lithium extraction from brine through a decoupled and membrane-free electrochemical cell design - Li, Zhen; Chen, I-Chun; Cao, Li; Liu, Xiaowei; Huang, Kuo-Wei; Lai, Zhiping (Science (American Association for the Advancement of Science), 2024)
The sustainability of lithium-based energy storage or conversion systems, e.g., lithium-ion batteries, can be enhanced by establishing methods of efficient lithium extraction from harsh brines. In this work, we describe a decoupled membrane-free electrochemical cell that cycles lithium ions between iron-phosphate electrodes and features cathode (brine) and anode (fresh water) compartments that are isolated from each other yet electrochemically connected through a pair of silver/silver-halide redox electrodes. This design is compatible with harsh brines having magnesium/lithium molar ratios of up to 3258 and lithium concentrations down to 0.15 millimolar, enabling the production of battery-grade (>99.95% pure) lithium carbonate. Energy savings of up to ~21.5% were realized by efficiently harvesting the osmotic energy of the brines. A pilot-scale cell with an electrode surface area of 33.75 square meters was used to realize lithium extraction from Dead Sea brine with a recovery rate of 84.0%. The centrality of lithium batteries to renewable energy infrastructure has motivated vigorous research into more efficient lithium sourcing. The oceans contain substantial aggregate quantities of lithium salts, but the comparatively low concentration makes them hard to separate from sodium and magnesium (see the Perspective by Darling). Li et al . now demonstrate a method inspired by the batteries themselves. In this method, iron phosphate electrodes can selectively intercalate lithium from salt water and then release it into fresh water. Charge balance is provided by silver oxidation and reduction at paired counterelectrodes in each medium, keeping all other cations on the salt side. In a different approach, Song et al . used plants as an inspiration to create a solar transpirational evaporator that extracts, stores, and releases lithium powered by sunlight. —Jake S. Yeston and Marc S. Lavine